The Vista (2014:Sept. 9) - University of Central Oklahoma (My University, 2014)
The Vista is the University of Central Oklahoma's student newspaper, published semiweekly except during examinations and holidays, and weekly during summer term. It was established in 1903 and is the longest continually published student newspaper in the state.
Keywords: Vista; UCO; Department of Journalism; College student newspapers and periodicals; University of Central Oklahoma; Edmond (Okla.)